Perlindungan dan Hak Asasi Manusia Bagi Orang Dengan Gangguan Jiwa: Sebuah Analisis Perspektif HAM Terhadap Pemasungan - Faliqul Ishbah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This jurnal addresses the sensitive issue of institutionalization of individuals with mental disorders from a Human Rights (HR) perspective. This study aims to analyze compliance and violations of HR in the practice of isntitutionalization for individuals with mental disorders. Research methods include literature analysis, case studies, and interviews with healthcare professionals and HR activists. The analysis reveals that institutionalization often involves violations of basic rights, such as the right to freedom, privacy, and protection from inhumane treatment. Attidionally, limited access to adequate mental healthcare is also a critical issue related to HR. In conclusion, this research underscores the need to strengthen HR protection for individuals with mental disorders, focusing on reducing institutionalization practices and enhancing access to quality mental healthcare. These steps are crucial in ensuring that the basic rights of every individual, including those experiencing mental disorders, are respected and safeguarded in line with international HR standards.